Building on Bildung in the 20th century – individual and institutional learning in Wittgenstein and Hesse - Edwards, G (2023)
This thesis will undertake a comparison of the figurative use of “games” in Philosophische Untersuchungen by Ludwig Wittgenstein and Das Glasperlenspiel by Hermann Hesse. Both works use “games” as an analogy to explore language use as a collective activity. ‘Bildung’ for the purposes of this thesis denotes the authors’ shared interest in how a good education should not only consist in applying oneself to scholarly study but also personal, moral development. I argue that ‘Sprachspiele’ and the ‘Glasperlenspiel’ are literary devices that the authors use in contrasting but complementary ways to explore the following questions: how do we help people to learn to think for themselves (to become well-rounded, independent thinkers) within an institutional environment that is necessarily conformist? How can students be taught to think for themselves, while also encouraging them to have the humility to listen to the opinions of others? The fact that games involve an element of freedom and spontaneity, while also being confined within rules that govern what can and cannot be done, means that the authors’ analogies were carefully chosen. This tension between freedom and rules within games reflects a tension at the heart of Bildung, identified by Georg Bollenbeck as dual process of ‘bilden’ and ‘sich bilden’ (whereby an individual is moulded by external forces, but also retains agency within their learning journey). By reading Wittgenstein and Hesse alongside one another, I would like to consider the question: If we were to think of our academic forms of life as a game, how might that change the way we think about what we do?